Hewlett-Packard Company : the departure of Mark Hurd (B) - Martin, Kevin (SAGE Knowledge. Cases., 2017)
After Mark Hurd steps down as CEO at Hewlett-Packard, Oracle hires him as co-president, as well as a member of their Board of Directors. A day later, Hewlett-Packard files a lawsuit against Hurd alleging he will not be able to do his new job without violating his confidentiality agreement. Tension arises between the two companies, which have been strategic business partners for 25 years. H-P also endures severe criticism from Oracles CEO, Larry Ellison.